2020
DOI: 10.1111/1541-4337.12629
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the status quo of polyphenols analysis: Part I—phytochemistry, bioactivity, interactions, and industrial uses

Abstract: Phytochemicals, especially polyphenols, are gaining more attention from both the scientific community and food, pharmaceutical, and cosmetics industries due to their implications in human health. In this line, lately new applications have emerged, and of great importance is the selection of accurate and reliable analytical methods for better evaluation of the quality of the end-products, which depends on diverse process variables as well as on the matrices and on the physicochemical properties of different pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 156 publications
0
20
0
Order By: Relevance
“…Therefore, the detected presence of the Flavonoid derivatives in Ammodaucus leucotrichus fruit extract was not surprising [10]. Different studies have shown that the Flavonoid glycosides possess a wide variety of pharmacological activities, such as antioxidant and anti-inflammatory [40,41]. Other compounds identification was based on the MS data; only some of them could be confirmed by previous research in this plant or taxonomical members [42][43][44][45][46][47][48][49][50][51].…”
Section: Chemical Characterizationsmentioning
confidence: 88%
“…Therefore, the detected presence of the Flavonoid derivatives in Ammodaucus leucotrichus fruit extract was not surprising [10]. Different studies have shown that the Flavonoid glycosides possess a wide variety of pharmacological activities, such as antioxidant and anti-inflammatory [40,41]. Other compounds identification was based on the MS data; only some of them could be confirmed by previous research in this plant or taxonomical members [42][43][44][45][46][47][48][49][50][51].…”
Section: Chemical Characterizationsmentioning
confidence: 88%
“…The chemical nature and biological potential of flavonoids depend on their structural class, degree of hydroxylation, other functional group substitutions, conjugations, and degree of polymerization, which categorize them in different subclasses ( Table 1 ) [ 91 ]. The different category of flavonoids varies in the arrangement of substitution of the C ring, while different compounds within a class differ in the pattern of substitution of the A and B rings.…”
Section: Polyphenols: Dietary Sources Chemistry and Medicinal Importancementioning
confidence: 99%
“…Studies have shown that verapamil inhibits the influx of Ca 2+ into the root apex of rice and wheat, while nifedipine prevents the development of root hair and pollen grain germination of Arabidopsis 16 . The calcium antagonist properties are displayed by a broad number of pure natural compounds, primarily coumarins, which have been identified and isolated from plants 14 , 17 .…”
Section: Introductionmentioning
confidence: 99%